Do LSP Textbooks Meet the Communicative Needs of L2 Learners? (LSP International Journal, 2017)
Needs analysis and description of language use in target situations are used to define the communicative demands of the target situation (Basturkmen & Elder, 2004). In spite of these steps taken in designing LSP courses, many L2 learners still face communication challenges in the workplace. Such is the case of L2 nursing students who experience various language related issues in their clinical placements. These results are not surprising given that L2 instruction traditionally targets the acquisition of the standard norm of the target language (Valdman, 2000). Indeed, L2 textbooks appear heavily influenced by the prescriptive view of language. This study focuses on the content analysis of French L2 commercial textbooks for nursing students. The materials were analyzed to identify the language use domains presented to students as well as the language features recommended to perform them. The results were then compared to transcriptions of 15 hours of recorded professional interactions between bilingual French-English nurses and French-speaking patients in a nursing home in Western Canada. The analysis reveals that commercial materials do not fulfill students’ communicative needs. The concept of pedagogical norm (Valdman, 1976, 2000) appears as a useful tool to improve the communicative content of LSP textbooks.